Antioxidant activity and photostability assessment of trans-resveratrol acrylate microspheres. (7th February 2019) - Pignatello, Rosario; Pecora, Tiziana M. G.; Cutuli, Giuseppa G.; Catalfo, Alfio; De Guidi, Guido; Ruozi, Barbara; Tosi, Giovanni; Cianciolo, Simona; Musumeci, Teresa
Abstract: Trans-resveratrol (RSV) was microencapsulated in Eudragit ® RS100 and RL100 resin blends. Lyophilized microspheres were characterized in the solid state for their micromeritic properties and drug loading. FT-IR, PXRD, and DSC analyzes suggested that RSV formed an intimate microcrystalline dispersion within the polymer network, also confirmed by SEM analysis. This produced a reduced degradation of RSV after storage at 40 °C, compared to the neat drug, and a protection of the drug from UV light-induced trans-cis isomerization (60% intact drug was found after 60 s irradiation at 350 nm, compared to 37% for the pure drug). Solubility and in vitro dissolution studies indicated that microencapsulation did not improve the dissolution pattern of RSV in simulated gastric and intestinal aqueous fluids. Evaluation of the in vitro antioxidant activity showed that, compared to the neat drug in aqueous solution, RSV loaded in the microspheres retained for a longer time, up to 22 days of incubation, the initial ORAC capacity. The present study thus demonstrated that Eudragit ® Retard resins can be used to easily produce micro-sized solid dispersions with RSV, for potential oral administration, contributing to ameliorate the physico-chemical stability and antioxidant activity of this compound.